Persepsi Pasien pada Sistem Pembayaran Kapitasi: Survey Pada Peserta Jaminan Kesehatan Nasional Di Puskesmas Kabupaten Demak - Indriyati Hadi Sulistyaningrum; Arifin Santoso; Fildza Huwaina Fathnin; Arizka Agus Solamanda; Atmarulin Dewi Nugrahaini (Pharmacon: Jurnal Farmasi Indonesia, 2022)
The National Health Insurance (JKN) is the government's effort to realize Universal Health Coverage (UHC). The capitation system implemented by the Puskesmas has an impact on the crisis of patient confidence in the quality of service obtained. This study was conducted to determine the patient's perception of the capitation system pharmaceutical services at the Demak Health Center. This observational study was conducted on 200 respondents from two puskesmas using the proportionalate random sampling technique. Patient perception data were analyzed with descriptive statistics of frequency distribution. The results of this study indicate that the majority of BPJS Kesehatan patients at the Demak District Health Center are women (69.5%), aged 33-47 years (41%), high school education level/equivalent (46.5%), working as housewives. (30.5%), income 1-2 million (36%), PBI membership status (75.5%). Perceptions of BPJS Health patients at the Demak District Health Center on indicators of high drug quality (83.3%), indicators of moderate amounts of drugs (57%), indicators of high drug availability (75.5%), high drug payment indicators (71.5%) . The conclusion from the results of this study is the patient's perception of "good" on quality indicators, drug availability, and drug payments. However, on the indicator of the number of drugs received, the patient's perception is still in the "moderate/enough" category. The Demak District Health Center needs to make efforts to increase the role of pharmacists in the drug counseling process when patients receive drugs at the Puskesmas.